Versorgungssicherheit mit Strom: Empirische Evidenz auf Basis der Inferred-Valuation-Methode - Manuel Frondel; Stephan Sommer; Lukas Tomberg (Zeitschrift für Wirtschaftspolitik, 2019)
Based on a survey among more than 5,000 German household heads, this article investigates their willingness to pay (WTP) for avoiding power outages using Contingent-Valuation-Methods (CVM). Alternatively, we ask respondents to estimate the WTP of a hypothetical household. This Inferred-Valuation-Method (IVM) is an approach introduced to reduce the hypothetical bias of stated WTP. Our empirical results indicate that, relative to the CVM, the IVM yields inflated WTP values, casting doubt on the validity of the IVM.
Keywords: D12; H41; Q41; 330; Contingent Valuation Method; Hypothetical Bias